2018
DOI: 10.1016/j.cmi.2018.01.015
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic treatment of infections caused by carbapenem-resistant Gram-negative bacilli: an international ESCMID cross-sectional survey among infectious diseases specialists practicing in large hospitals

Abstract: Combination therapy was the preferred treatment strategy for infections caused by carbapenem-resistant Gram-negative bacteria among hospital representatives, even though high-quality evidence for carbapenem-based combination therapy is lacking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
47
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(47 citation statements)
references
References 29 publications
(21 reference statements)
0
47
0
Order By: Relevance
“…Combination therapies possess potential additional benefits of a wider activity spectrum and a synergistic effect and so may be effective in combating infections and improving clinical outcomes [31,32]. Real-life data in patients with multidrug-resistant Gram-negative infections seems to suggest that medical doctors use combination therapies to increase effectiveness and reduce resistance risk [33]. However, this evidence is strongly biased by the retrospective nature of most studies and the lack of randomized clinical trials and appropriate controls in cohort studies [34].…”
Section: Discussionmentioning
confidence: 99%
“…Combination therapies possess potential additional benefits of a wider activity spectrum and a synergistic effect and so may be effective in combating infections and improving clinical outcomes [31,32]. Real-life data in patients with multidrug-resistant Gram-negative infections seems to suggest that medical doctors use combination therapies to increase effectiveness and reduce resistance risk [33]. However, this evidence is strongly biased by the retrospective nature of most studies and the lack of randomized clinical trials and appropriate controls in cohort studies [34].…”
Section: Discussionmentioning
confidence: 99%
“…To counter the threat of resistance, RF should be preserved, as its use, in combination therapy for nonmycobacterial infections, is ever more frequent. In addition to the well‐known use in prosthetic valve endocarditis (PVE) therapy (Habib et al, ) (given its ability to penetrate through biofilm), other possible uses are either currently accepted or under investigation: RF use in MRSA infections (Purrello et al, ), antibiotic regimens with RF for targeted treatment of infections caused by extensively drug‐resistant carbapenem‐resistant Pseudomonas aeruginosa (XDR CRPa)/ Acinetobacter baumannii (XDR CRAb) (Papst et al, ), minocycline/rifampicin‐impregnated central venous catheters for preventing central line‐associated bloodstream infections (CLABSIs) in the intensive care unit (ICU) setting (Bonne et al, ), and telavancin combined with rifampicin against MRSA in an in vitro biofilm model (Jahanbakhsh, Singh, Yim, Rose, & Rybak, ) are just a few examples. for pharmacokinetic explanations, it is demonstrated that co‐treatment with RF reduces CL plasma concentrations, with a probable drug underexposure at the infection site (Curis et al, ; Join‐Lambert et al, ). This phenomenon is to be correlated with the RF ability to induce the cytochrome CYP3A4 (responsible for CL metabolism) (Sousa, Pozniak, & Boffito, ). for RF possible effect on the intestinal microbiota, nowadays, when considering a long‐lasting antibiotic therapy, the present authors cannot help but consider its effect on the intestinal microbiota.…”
Section: Discussionmentioning
confidence: 99%
“…All the patients in our study were treated with effective antibiotics for at least one day (24h), and we accounted for the time when the effective antibiotics started. There is debate concerning which antibiotics are the most effective in CRGNB 26 or VRE. 7 This uncertainty hindered the exploration of treatment.…”
Section: Discussionmentioning
confidence: 99%